Adipocyte‐Specific Enhancement of Angiotensin II Type 1 Receptor‐Associated Protein Ameliorates Diet‐Induced Visceral Obesity and Insulin Resistance. Issue 3 (March 2017) - Azushima, Kengo; Ohki, Kohji; Wakui, Hiromichi; Uneda, Kazushi; Haku, Sona; Kobayashi, Ryu; Haruhara, Kotaro; Kinguchi, Sho; Matsuda, Miyuki; Maeda, Akinobu; Toya, Yoshiyuki; Yamashita, Akio; et al.
Abstract : Background: The renin–angiotensin system has a pivotal role in the pathophysiology of visceral obesity. Angiotensin II type 1 receptor (AT1R) is a major player in the signal transduction of the renin–angiotensin system, and the overactivation of this signaling contributes to the progression of visceral obesity. We have shown that the AT1R‐associated protein (ATRAP) promotes AT1R internalization from the cell surface into cytoplasm along with the suppression of overactivation of tissue AT1R signaling. In this study, we examined whether the enhancement of adipose ATRAP expression could efficiently prevent diet‐induced visceral obesity and insulin resistance. Methods and Results: We generated adipocyte‐specific ATRAP transgenic mice using a 5.4‐kb adiponectin promoter, and transgenic mice and littermate control mice were fed either a low‐ or high‐fat diet for 10 weeks. Although the physiological phenotypes of the transgenic and control mice fed a low‐fat diet were comparable, the transgenic mice exhibited significant protection against high‐fat diet–induced adiposity, adipocyte hypertrophy, and insulin resistance concomitant with an attenuation of adipose inflammation, macrophage infiltration, and adipokine dysregulation. In addition, when mice were fed a high‐fat diet, the adipose expression of glucose transporter type 4 was significantly elevated and the level of adipose phospho‐p38 mitogen‐activated protein kinase was significantly attenuated in the transgenic mice compared with control mice. Conclusions: Results presented in this study suggested that the enhancement in adipose ATRAP plays a protective role against the development of diet‐induced visceral obesity and insulin resistance through improvement of adipose inflammation and function via the suppression of overactivation of adipose AT1R signaling. Consequently, adipose tissue ATRAP is suggested to be an effective therapeutic target for the treatment of visceral obesity.